PENGAWASAN PENYALURAN BANTUAN PANGAN NON TUNAI (BPNT) DI DESA PAUH ANGIT KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Septi Wiranda; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The target group of beneficiaries of the Non-Cash Food Assistance Program (BPNT) complained that in the distribution of BPNT there were often constraints on utilization, namely empty / late, blocked and lost balances due to lack of coordination and supervision at the time of distribution. The purpose of this study was to determine the supervision of the distribution of non-cash food aid in Pauh Angit Village, Pangean District, Kuantan Singingi Regency. This research uses the theory of Manullang (2015) supervision which consists of 3 indicators, namely setting a measurement tool (standard), conducting an assessment, and carrying out corrective actions. This research uses a qualitative method with a case study approach. Informants in this study were the Head of  Social Assistance and Security of Kuantan Singingi Regency, the Social Welfare Development Section of the Kuantan Singingi District Office, the BPNT companion of Pauh Angit Village, the TKSK chair, the head of the Pauh Angit Village E-warung, the non-KPM beneficiary family (BPNT). Informants were taken using snowball sampling. Data collection is done by observation, interviews, documentation and literature study. Data analysis uses linear and hierarchical approaches. The results showed that the supervision of the distribution of non-cash food aid (BPNT) was still low so distribution, distribution was still low and not yet on target. The inhibiting factors in the supervision of the distribution of non-cash food assistance (BPNT) in the coordination and outreach of the BPNT program are low, awareness and quality of  implementing resources for the BPNT program is low and the attitude of the BPNT distribution team is not yet optimal. So that there is a need for socialization and training to supervise the distribution of non-cash food aid. Keywords: Supervision, Distribution, Non-Cash Food Assistance Program (BPNT).